Strategies of Indonesian Kindergarten Teachers for Developing Children’s Prosocial Behaviour - Arifiyanti, Nurul; Dwiningrum, Siti Irene Astuti; Syamsudin , Amir (Journal of Education Culture and Society, 2025)
Aim. This study aimed to investigate the methods utilised by kindergarten teachers in Indonesia to cultivate prosocial behaviour in young children, acknowledging the potential impact of insufficient prosocial behaviour on both social and academic progress. Method. Using a qualitative approach, the research gathered insights through open-ended inquiries in virtual interviews with 49 kindergarten educators throughout Indonesia. The data collected was thematically analysed, focusing on teachers’ observations and approaches to encourage prosocial conduct. Results. The examination revealed that approximately 91.8% of teachers noted deficiencies in prosocial behaviour among confident children, particularly citing challenges in sharing and cooperation. Teachers implemented diverse strategies such as direct engagement with students, facilitating collaborative activities, fostering prosocial values, establishing classroom rules, and modelling prosocial behaviour. Collaborative learning frameworks emerged as the predominant method employed to bolster prosocial development. Conclusion. The outcomes of this investigation provide practical guidance for early childhood teachers to refine classroom methodologies and exemplify behaviour that fosters prosocial skills in young learners. Moreover, this study contributes to unravelling effective techniques for cultivating prosocial behaviour within Indonesia’s cultural and educational landscape, addressing a notable gap in local research on early childhood education.